Modeling user’s trust in M-commerce acceptance: A conceptual framework in context of Pakistan - Rind, M Malook; Koondhar, M Yaqoob; Hyder, Mansoor; Shah, Asadullah (The Institute of Electrical and Electronics Engineers, Inc., 2016)
With the emergence of Intern ate and world wide web traditional business got new opportunity to complete globally. Traditional bricks-and-mortar business became electronic business ( e-business) by utilizing information and communication technology (ICT) tools. A new term of Mobile Commerce (M-Commerce) has created tremendous spectrum of business opportunities for businesses. Although there has been large scale adoption of M-Commerce in developing economies, but little growth is observed in developing economies such as Pakistan. There are doubts that users of M-Commerce demonstrate a lack of enthusiasm, which may be due to lack of trustworthiness. Based on the well-known and widely used technology acceptance model (TAM), this research study provides the conceptual framework, underpinning the relationship of trust with adoption of M-Commerce in Pakistan. The aim of this paper is to study the role of trust and its relationship with the acceptance of M-Commerce in Pakistan.